2008
DOI: 10.1007/s00497-008-0076-x
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco pollen tubes as cellular models for ion dynamics: improved spatial and temporal resolution of extracellular flux and free cytosolic concentration of calcium and protons using pHluorin and YC3.1 CaMeleon

Abstract: The presence of both calcium (Ca 2+ ) and proton (H + ) apical gradients is necessary for polarized cell elongation to occur in pollen tubes. So far, most of these studies have been carried out in lily pollen tubes, using chemical probes. Yet, lily is a refractory model for molecular genetics, with no easy protocol available for the construction of stable transgenic lines. Tobacco, however, is well suited for both transformation and cell biology, with sexual organs that are accessible, easy to handle and visua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
64
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(69 citation statements)
references
References 44 publications
4
64
1
Order By: Relevance
“…Correlation between a Cytosolic Anion Concentration Gradient and Ca 2+ Homeostasis at the Tip On in vitro growing conditions (especially in tobacco and lily), it is well established that pollen tubes tend to display oscillations in growth rate, which are associated with changes in tip-localized [Ca 2+ ] cyt changes in various species (Heslop-Harrison et al, 1985;Holdaway-Clarke et al, 1997;Camacho et al, 2000;Lazzaro et al, 2005;Michard et al, 2008). A set of CPKs was recently demonstrated to regulate anion channel activity in guard cells (Geiger et al, 2009b(Geiger et al, , 2011Brandt et al, 2012;Scherzer et al, 2012).…”
Section: Online)mentioning
confidence: 99%
See 2 more Smart Citations
“…Correlation between a Cytosolic Anion Concentration Gradient and Ca 2+ Homeostasis at the Tip On in vitro growing conditions (especially in tobacco and lily), it is well established that pollen tubes tend to display oscillations in growth rate, which are associated with changes in tip-localized [Ca 2+ ] cyt changes in various species (Heslop-Harrison et al, 1985;Holdaway-Clarke et al, 1997;Camacho et al, 2000;Lazzaro et al, 2005;Michard et al, 2008). A set of CPKs was recently demonstrated to regulate anion channel activity in guard cells (Geiger et al, 2009b(Geiger et al, , 2011Brandt et al, 2012;Scherzer et al, 2012).…”
Section: Online)mentioning
confidence: 99%
“…The activity of the K + -inward rectifier SPIK was recently demonstrated to be CPK dependent (Zhao et al, 2013). Likewise, it is well established that intracellular H + and Ca 2+ gradients generated at the pollen tube tip are closely linked to pollen tube guidance, growth direction, and speed (Pierson et al, 1996;Holdaway-Clarke et al, 1997;Certal et al, 2008;Michard et al, 2008). Many of these physiological processes are interconnected, rendering the analysis of the Ca 2+ signaling cascades difficult.…”
Section: Correlation Between Anion and Ca 2+ Homeostasismentioning
confidence: 99%
See 1 more Smart Citation
“…One reason for the popularity of FRET is that, in addition to its use for detecting PPIs, it also can be used with genetically encoded, unimolecular sensors, and it can be used in native species in vivo (Frommer et al, 2009;Uslu and Grossmann, 2016). A range of sensor molecules have been developed or optimized for use in plants, enabling the detection of calcium (Krebs et al, 2012;Wagner et al, 2015), phosphate (Mukherjee et al, 2015), zinc (Lanquar et al, 2014), and abscisic acid (Jones et al, 2014a) as well as physiochemical states of the cell such as pH (Michard et al, 2008) and membrane voltage . One great advantage of using intramolecular FRET sensors lies in the theoretically equal stoichiometry, rendering ratiometric readouts independent of sensor concentration.…”
Section: Fret: Lifetime Versus Intensitymentioning
confidence: 99%
“…Actually, it has been shown that pH changes exert a profound effect on most biological processes, including nutrient uptake, cell growth and plantmicrobe interactions (Feijó et al, 1999;Felle, 2001;michard et al, 2008). Previously, it was postulated by A.r.…”
Section: Changes On Host and Fungal Ionome: Proton And Calcium Dynamicsmentioning
confidence: 99%